Emotional Intelligence and The Perceived Influence on Job Satisfaction: An Exploratory Study with Nurses - Diana Silva COSTA; João Leite RIBEIRO; Delfina GOMES (Communications of International Proceedings, 2024)
Composed of a multiplicity of capabilities inherently linked to the emotions of individuals, Emotional Intelligence has been drawing the attention of the academic and scientific community, as well as different organizations, regarding its importance- and role in the current job market. In this sense, the present study intends to understand how nurses perceive and value emotional intelligence from the Portuguese National Health Service, how these professionals define the concept of job satisfaction, and what they consider to be its causes. A qualitative approach was followed according to the interpretative paradigm and the exploratory research to fulfill the proposed objectives. As for the data collection method, twenty-five semi-structured interviews were carried out with nurses who exercise or have already exercised their profession in the National Health Service. In turn, the content analysis method was used to analyze the opinions and perspectives of professionals on the subject in question. The study concludes by highlighting that the participants attribute importance to Emotional Intelligence for their well-being, improvement of their practice, and interaction with users. Moreover, different ways were explored through which the components of Emotional Intelligence, in the perception of these nursing professionals, can positively influence the satisfaction they feel in their jobs.
Keywords: Emotional Intelligence; Job Satisfaction; Nurses